VISTA CONOSCENZA, PAROLA: LO “SCHEMA DEL CONTENITORE” APPLICATO A UN CASO DI POLISEMIA INDOEUROPEA - Marianna POZZA (Studia Universitatis Babeş-Bolyai. Philologia, 2021)
View, Knowledge, Word: The Container Image-Schema Applied to a Case of Proto-Indo-European Polysemy. The present discussion aims at reconsidering the theoretical process of knowledge in some ancient Indo-European languages in the light of the prerequisites offered by cognitive linguistics and prototype theory. Thanks to the dynamic pattern of the Container Image-Schema – which is a primitive mental structure – some historical outcomes of a polysemic Indo-European root will be discussed in order to place them within the continuum of the semantic space in which the container is located.